The sound of misogyny: sexual harassment and sexual violence in the music industry - McCarry, Melanie; Käkelä, Emmaleena; Jones, Cassandra; Manoussaki, Kallia (Journal of Gender-Based Violence, 2023)
The cultural and creative industries are the fastest growing industries in the UK (). Stakeholder engagement, media reporting, anecdotal evidence and emerging research suggests that there are endemic levels of sexual harassment and sexualised violence within the music industry that can be described as widespread, systemic and normalised. This article reviews the literature on sexual harassment and sexualised violence in the music industry, examining gender stratifications and inequalities within the music industry with a focus on UK, Australian and US studies. The music industry is not a singular entity but instead, is an agglomeration of many different sub-sectors predominantly consisting of three interconnected spheres of music recording and distribution, music publishing and licensing, and live performance. This paper references Kelly’s (; ; ) theorisations on conducive contexts and the continuum of violence to argue that historical and entrenched misogyny and sexism along with the lack of regulation, process and governing frameworks create conditions for both the maintenance of gender inequality and the perpetuation of sexual harassment and sexualised violence within the music industry. Consequently, both the cultural context and the practice of misogyny (in this case sexual harassment and sexualised violence) within the music industry are mutually supporting and reinforcing.
Publisher: Policy Press Section: Journal of Gender-Based Violence
Keywords: Misogyny; Music; Myriam

Music as Labour: Inequalities and Activism in the Past and Present - Abfalter, Dagmar; Reitsamer, Rosa (Taylor & Francis, 2022)
This book brings together research at the intersection of music, cultural industries, management, antiracist politics and gender studies to analyse music as labour, in particular highlighting social inequalities and activism. Providing insights into labour processes and practices, the authors investigate the changing role of manifold actors, institutions and technologies and the corresponding shifts in the valuation and evaluation of music achievements that have shaped the relationship between music, labour, the economy and politics. With research into a variety of geographic regions, chapters shed light on the various ways by which musicians’ work is performed, constructed and managed at different times and show that musicians’ working practices have been marked by precarity, insecurity and short-term contracts long before capitalism invited everybody to ‘be creative’. In doing so, they specifically examine the dynamics in music professions and educational institutions, as well as gatekeepers and mechanisms of inclusion and exclusion. With a specific emphasis on inequalities in the music industries, this book will be essential reading for scholars seeking to understand the collective actions and initiatives that foster participation, inclusion, diversity and fair pay amongst musicians and other workers.
Accepted: 2022-05-18T09:38:24Z
Keywords: Music; Myriam; Personnel and human resources management; bic Book Industry Communication::A The arts::AV Music; bic Book Industry Communication::K Economics; business & management::KJ Business & management::KJM Management & management techniques::KJMV Management of specific areas::KJMV2 Personnel & human resources management; finance

In Her Own Words: Documenting the Current Realities of Women-in-Jazz - Manfredo, Alexandra, Kiernan Steiner (The Routledge Companion to Jazz and Gender, 2022)
Since the inception of jazz, the lives and experiences of women-in-jazz have been inadequately documented and archived, which has led to a lack of female representation in the jazz community. During the recent resurgence of the #MeToo Movement, many women-in-jazz bravely shared stories of sexual discrimination and harassment. As the jazz community continues to address the gender disparity, women’s stories need to be centered in order to address current realities of women-in-jazz. By documenting the experiences of women-in-jazz in higher education as students, educators and performers, sexual discrimination and harassment must be considered as contributing factors of the gender disparity in jazz.
Num Pages: 14
Keywords: Jazz; Music; Myriam

Raising Their Voices: Independent Review into Sexual Harm, Sexual Harassment, and Systemic Discrimination in the National Music Industry - Shehadie, Alexandra; The Review Team (Support Act, 2022)
Keywords: Bibliographie; Nettoyer

Normalising sexualised violence in popular culture: eroding, erasing and controlling women in rock music - Hill, Rosemary Lucy; Richards, Daisy; Savigny, Heather (Feminist Media Studies, 2021)
How does music play a role in normalising men’s sexual violence towards women? Using mainstream rock and metal music as an illustrative case study, we offer a nuanced account of the ways in which men’s sexual violence is normalised. Using a definition of sexual violence drawn from Liz Kelly’s notion of a continuum, which reframes sexual violence as the loss of women’s ability to control sexual experiences, we explore the ways in which sexual violence is a prevalent lyrical and audio-visual component of rock and metal songs. We show that a pernicious theme of rock and metal over the last 25 years is the erosion of women’s ability to refuse sexual activity and to have voice and be heard. We argue that this erosion of women’s consent takes place through the representational use of emotional abuse, controlling/coercive behaviour, and through the objectification of women. The erasure of consent presented through these methods becomes a key means of establishing sexual control. Through manipulation, the confusion of what counts as sexual violence and how it is defined, men’s sexual violence against women is normalised.
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2021.1902368
Keywords: Feminism; music video; rock lyrics; rock music; sexual violence

Kesha’s Comeback and the Stakes of Live Performance: Connecting through Trauma at the 2018 Grammy Awards - Hearfield, Katelyn (Journal of Musicological Research, 2021)
The use of live popular music performance as a platform to address gendered and sexual violence and trauma within the popular music industry can be demonstrated through the analysis of Kesha’s performance of “Praying” at the 2018 Grammy Awards. Analyzing the artist’s vocal and artistic delivery, in addition to her public persona following her allegations of sexual abuse against producer Lukasz Gottwald (Dr. Luke), illustrates how live performance—building on and contrasting with social media campaigns, such as #FreeKesha and #MeToo, and studio recordings—is a uniquely effective mode of processing individual and collective trauma.
Keywords: Bibliographie; Nettoyer

For the Love of Music: Ending Sexual Harassment in the Music Industry - Musicians’ Union (2021)
Keywords: Bibliographie; Nettoyer

Sexual Violence and Gender Equality in Grassroots Music Venues: How to Facilitate Change - Hill, Rosemary Lucy; Megson, Molly (IASPM Journal, 2020)
Sexual violence in the music industry is known to impact negatively on women’s participation. We examine how grassroots venues and promoters can implement changes to tackle sexual violence and work towards gender equality. We draw on UK-based, impact-focused research which sought to raise awareness of sexual violence, and to facilitate anti-violence changes within organisations. We find that working across a city’s music scene and engaging with oversight organisations such as local authorities can aid in persuading venues and promoters to seek training. However, for individuals leading on changes, personal experiences of sexual violence as a victim/survivor or bystander are important factors in their decision. We conclude that men in the music industry need to become more aware of the need for change, and willing to act on that awareness; and that more women need to own, manage, and run venues and events.
Keywords: Bibliographie; Gender; Nettoyer; live music; music industry; music venues; prevention; sexual violence

'Urban' no more: black British music execs call for industry reforms (the Guardian, 2020)
Open letter from new group seeks action on racism and better career development
Section: Music

Mobilisations féministes sur Facebook et Twitter: Le cas du mouvement #StopCultureDuViol au Québec - Hübner, Lena A.; Pilote, Anne-Marie (Terminal, 2020)

Gendered Violence at International Festivals: An Interdisciplinary Perspective - Platt, Louise; Finkel, Rebecca (Routledge, 2020)
Gendered Violence at International Festivals is a groundbreaking collection that focusses on this highly important social issue for the first time. Including a diverse range of interdisciplinary studies on the issue, the book contests the widely held notion that festivals are temporal spaces free from structural sexism, inequalities or gender power dynamics. Rather, they are spaces where these concerns are enhanced and enacted more freely and where the experiential environment is used as an excuse or as an opportunity to victim blame and shame. In this emerging and under-researched area, the chapters not only present original work in terms of topics but also in theoretical and methodological approaches. All of the chapters are cross- or interdisciplinary, drawing on gender, sexualities, cultural and ethnicity studies. Studies from a range of highly regarded academics based around the world examine the subject by looking at examples from a wide range of destinations, including Spain, Argentina, Nigeria, Zimbabwe, Australia, Canada and the UK. This significant book progresses understanding and debates about gendered festival experiences and emphasises the symbolic and physical violence often associated with them. This will be of great interest to, undergraduate and postgraduate students and academics in the field of Events Studies. It will also be of use to practitioners or non-profit workers in the festival industries, including festival management organisations and planning committees.
Google-Books-ID: Q6bYDwAAQBAJ
Keywords: Business & Economics / Industries / Hospitality; Travel & Tourism

‘Put some balls on that woman’: Gendered repertoires of inequality in screen composers’ careers - Cannizzo, Fabian; Strong, Catherine (Gender, Work & Organization, 2020)
This study contributes to debates about gendered career outcomes in the creative industries using data collected in interviews with Australian screen composers. We identify how gendered inequalities are legitimated through professional norms by comparing the responses of screen composers on barriers to women’s advancement. The article explores how three distinct interpretive repertoires help reproduce the gender inequality regime present in the screen composition field. These repertoires are ‘art vs. equality’, where working towards equality can be framed as antithetical to artistic ideals; ‘gendered music’, where men and women are posited as making fundamentally different types of music; and ‘confidence’, where men are framed as innately possessing certain entrepreneurial skills vital to success in the creative industries, while women both shoulder the blame for not possessing such skills and recognize the risks inherent for them in performing confidence. By focusing on repertoires, this study describes the means by which gender-based discrimination is made overt and offered justification among screen composers, posing challenges to organizations and individuals seeking to address gender inequality in the profession.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/gwao.12496
Keywords: Australia; Musique de film; Myriam; composers; creative industries; cultural industries; gender inequality; sexism

Teaching Tertiary music in the #metoo era - Devenish, Louise; Sun, Cecilia; Hope, Cat; Tomlinson, Vanessa (Tempo, 2020)
Abstract Over the past two decades significant changes in approaches to gender equity have taken place in the fields of contemporary music and music research. However, women in music are still disadvantaged in terms of income, inclusion and professional opportunities. In Australia a national approach to improving gender equity in music has begun to emerge as once-controversial strategies trialled by four tertiary institutions have become established practices. This article discusses successful inclusion strategies for women in music, including the commitment to gender-balanced programming across all concerts at Queensland Conservatorium of Music by 2025, the introduction of mandatory quotas in recital programmes at Monash University, mentoring programmes for women composers at Sydney Conservatorium of Music, and the development of coursework devoted to women in music at The University of Western Australia, as well as other initiatives that have emerged from them, both within and beyond the institution. Each approach is examined in the context of broader global discussions around gender and feminism. The public willingness to engage in discussions over sexual harassment, sexual assault and gender discrimination in the workplace that has resulted from the #MeToo movement is cited as key in influencing the engagement of students and professionals with these strategies and subsequent influence on performance practices, project development and presentational formats in new music.
Keywords: Myriam

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention